Immunological responses in patients with tuberculosis and in vivo effects of acetyl-L-carnitine oral administration - Emilio Jirillo; Maria Altamura; Carlo Marcuccio; Cosimo Tortorella; Claudio De Simone; Salvatore Antonaci (Mediators of Inflammation)
Tuberculosis (TBC) is characterized by a complex immune response which parallels the clinical course of the disease. In this respect, acquired resistance, delayed hypersensitivity reaction and anergy are the main types of immune reactivity to mycobacterial antigens. In view of the presence of nonspecific and specific immune deficits in TBC patients, a clinical trial was carried out in a group of 20 individuals with active pulmonary TBC by oral administration of acetyl-L-carnitine (ALC). This drug, which has been shown to possess immunomodulating activities, was able to upregulate the T-dependent antibacterial activity in TBC patients after 30 days' treatment, while the same activity decreased in patients receiving placebo only. On the other hand, ALC did not modify serum levels of tumour necrosis factor-α, in the same individuals. This cytokine plays a detrimental rather than beneficial role in TBC pathogenesis. In the light of these data, ALC seems to be a powerful immunomodulator in the course of Mycobacterium tuberculosis infection and other mycobacteriosis.